Study of english borrowing word in indonesian as found in habibie & ainun movie - Dewi, Ni Komang Shintia Pradnyana; Sulatra, I Komang; Putra, I G. B. Wahyu Nugraha (Institut Pariwisata dan Bisnis Internasional, 2022)
This research concerns with borrowing words in Indonesian as found in the movie. This research aims at (1) to identify the types of borrowing word; and (2) to identify the adaptations of borrowing words used in Habibie & Ainun movie. The method used in this research is descriptive qualitative for analyzing the data. This study used the theory of Haugen in (Grosjean 1982) that was the type and the adaptation of borrowing words. The results showed that there were 2 types of borrowing words found in the data source namely loanword and loan shift. For the adaptation process, there are 2 kinds of adaptation processes found here, namely phonological adaptation and morphological adaptation. The occurrence of pure loan words was dominant compared to the other types. Borrowing words are often found in online and print media such as television, newspapers, magazines, internet, etc. Borrowing words are analyzed in this study to provide knowledge about the existence of word borrowing in Indonesian. The Indonesian borrows many words in English, of course increasing the number of vocabularies in Indonesian.